Cześć!
a)
[tex]-2x^2-6x+8=0 \ \ /:(-2)\\\\x^2+3x-4=0\\\\a=1, \ b=3, \ c=-4\\\\\Delta=b^2-4ac\rightarrow3^2-4\cdot1\cdot(-4)=9+16=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\x_1=\frac{-b-\sqrt{\Delta}}{2a}\rightarrow\frac{-3-5}{2\cdot1}=\frac{-8}{2}=\boxed{-4}\\\\x_2=\frac{-b+\sqrt{\Delta}}{2a}\rightarrow\frac{-3+5}{2\cdot1}=\frac{2}{2}=\boxed1[/tex]
b)
[tex]2x-3x^2>0 \ \ /\cdot(-1)\\\\3x^2-2x<0\\\\3x(x-\frac{2}{3})<0\\\\3x=0 \ \ \ \vee \ \ \ x-\frac{2}{3}=0\\\\x_1=0 \ \ \ \vee \ \ \ x_2=\frac{2}{3}\\\\\huge\boxed{x\in(0;\frac{2}{3})}[/tex]